Development Of Educaplay-Based Educational Game Media in Ipas Subject On Energy Around Us for Grade 3 SDN Bulang 1 - Fitri Yuliatin; Didit Yulian Kasdriyanto; Faridahtul Jannah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to develop an Educaplay-based educational game for the Natural and Social Sciences (IPAS) subject specifically the topic of